Retinal Stem/Progenitor Cells Derived From Adult Müller Glia for the Treatment of Retinal Degeneration - Too, Lay Khoon; Simunovic, Matthew P. (Frontiers in Cell and Developmental Biology, 2021)
Over the past two decades, progress in our understanding of glial function has been revolutionary. Within the retina, a subset of glial cells termed the “Müller glia (MG),” have been demonstrated to play key roles in retinal homeostasis, structure and metabolism. Additionally, MG have also been shown to possess the regenerative capacity that varies across species. In teleost fish, MG respond to injury by reprogramming into stem-like cells capable of regenerating lost tissue. The expression of stem/progenitor cell markers has been demonstrated broadly in mammalian MG, including human MG, but their in vivo regenerative capacity appears evolutionarily limited. Advances in stem cell therapy have progressively elucidated critical mechanisms underlying innate MG reprogramming in teleost fish, which have shown promising results when applied to rodents. Furthermore, when cultured ex vivo, MG from mammals can differentiate into several retina cell types. In this review, we will explore the reparative and regenerative potential of MG in cellular therapy approaches, and outline our current understanding of embryonic retinal development, the stem-cell potential of MG in adult vertebrate retina (including human), and microenvironmental cues that guide MG reprogramming.